Fabrication and characterization of SiO2-embedded castor oil-based membrane (Ricinus communis L) for aqueous Fe adsorption - Nisah, Khairun; Khairi, Miratul; Sukandar , Redha; Nuzlia, Cut; Nasution, Reni S.; Ilhami, Syarifa; Chiari, Williams (Narra Sains Indonesia, 2024)
Castor seed oil (Ricinus communis L) can be utilized for the manufacturing of membranes reacted with toluene diisocyanate (TDI). The aim of this study was to examine the effect and membrane characteristics of castor seed oil with a combination of silica used as an adsorbent, with a combination of silica (SiO2) 0.5 mg, 1 mg, 1.5 mg, and 2 mg. The initial analysis of the membrane was carried out with a swelling test of 1.5 mg of silica variation to obtain the most ideal result of 200%. The best chemical resistance characterization occurred at a variation of 1.5 mg of silica. Further characterization, particularly the FTIR test, thermal test, mechanical test, and SEM test, showed that there were Si-O groups and amine groups (NH2), and on the membrane there were groups OH, C=O, and NH. The thermal characterization of the silica membrane (1.5 mg) gave the greatest residue concentration, measuring 3.2%. In mechanical terms, the silica membrane has a higher elongation value than the membrane. In SEM characterization, the silica membrane has holes and is solid. This study indicated that the highest drop in Fe metal occurred at an immersion period of 6 hours with a combination of silica with a flux value of 9.25 L/m2 hour and a rejection value of 0.098%.